Physiotherapy clinical educators' perspectives on a fitness to practice initiative. (2nd January 2018) - Lo, Kristin; Curtis, Heather; Francis-Cracknell, Alison; Maloney, Stephen; Nickson, Wendy; Bearman, Margaret; Keating, Jennifer L
ABSTRACT: Context : Health practitioner registration boards require health professionals to evaluate and maintain "fitness to practice" (FTP). This encompasses the professional behavior, clinical competence, and freedom from impairment required for safe and effective service provision. We developed and implemented policies to promote student self-assessment and support of FTP that were pre-emptive and designed to be helpful and sought clinician feedback on this initiative. Method : An innovative student-centered FTP approach was devised with consideration of defensible ethico-legal practice. A survey explored clinical educators' perceptions of the FTP policy and the associated education and support. Closed and open survey questions were analyzed using descriptive statistics, qualitative evaluation, and thematic analysis. Results : Seventy-nine physiotherapy clinical educators from 34 sites across eight Australian health services returned surveys. Educators had positive perceptions of policy components, particularly incorporating professionalism as a hurdle requirement and the attendance and incident reporting policies. Conclusions : The benefits of a student-centered FTP approach included clarity and consistency in managing FTP issues and facilitation of student awareness through active engagement in maintaining their FTP. To our knowledge, this paper is the first to report a comprehensive approach to the range of FTP issues incorporating student self-declaration of issues that may affect desirable progression through clinical placements. The policy and program of education and support are likely to be generalizable to health professional training programs that utilize workplace training.